The Moral Project of Childhood motherhood, material life, and early children's consumer culture - Cook, Daniel Thomas 1961- (New York University Press, 2020)
Examines the Protestant origins of motherhood and the child consumer Throughout history, the responsibility for children's moral well-being has fallen into the laps of mothers. In The Moral Project of Childhood, the noted childhood studies scholar Daniel Thomas Cook illustrates how mothers in the nineteenth-century United States meticulously managed their children's needs and wants, pleasures and pains, through the material world so as to produce the "child" as a moral project. Drawing on a century of religiously-oriented child care advice in women's periodicals, he examines how children ultimately came to be understood by mothers-and later, by commercial actors-as consumers. From concerns about taste, to forms of discipline and punishment, to play and toys, Cook delves into the social politics of motherhood, historical anxieties about childhood, and early children's consumer culture. An engaging read, The Moral Project of Childhood provides a rich cultural history of childhood
Keywords: Geschichte 1800-1899; Allowances; child; Children's Rights; Children's rooms; consumption; Creative Child; Depravity; Developmentalism; Discipline; Empathy; Feminization; Girlhood; Malleability; Market Research; Memory; Money; Moral architecture; Moral project; Motherhood; Pedagogy; Pleasure; Pre-capitalist child; Predestination; Property; Provisioning; Punishment; Reward; Simplicity; Subjectivity; Taste; Value; interiority; materiality; morality; mother; SOCIAL SCIENCE / Sociology of Religion; Child consumers; Consumers; Erziehung; Mutter; Verantwortung; Kind; USA